2023
DOI: 10.1039/d3tb00208j
|View full text |Cite|
|
Sign up to set email alerts
|

Additive manufacturing of barium-doped calcium silicate/poly-ε-caprolactone scaffolds to activate CaSR and AKT signalling and osteogenic differentiation of mesenchymal stem cells

Abstract: The 3D-printed scaffold is suitable for patient-specific implant preparation for bone regeneration in large-scale critical bone defects. In addition, these scaffolds should have mechanical and biological properties similar to those...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Moreover, the Ca 2+ concentration played a critical role in this process. This factor can regulate osteoblast differentiation by activating calcium-sensing receptors and increasing Ca 2+ influx into osteoblasts (Chiu et al, 2023). In addition to these potential reasons, a recent study reported that Cu 2+ could promote higher expression of osteogenesis-related genes, and mineralization of the cells (Burghardt et al, 2015).…”
Section: Scaffolds Promote Osteogenic Differentiation Of Bmscs In Vitromentioning
confidence: 99%
“…Moreover, the Ca 2+ concentration played a critical role in this process. This factor can regulate osteoblast differentiation by activating calcium-sensing receptors and increasing Ca 2+ influx into osteoblasts (Chiu et al, 2023). In addition to these potential reasons, a recent study reported that Cu 2+ could promote higher expression of osteogenesis-related genes, and mineralization of the cells (Burghardt et al, 2015).…”
Section: Scaffolds Promote Osteogenic Differentiation Of Bmscs In Vitromentioning
confidence: 99%
“…Recently, significant attention has been directed toward the role of barium in bone repair and regeneration, particularly in the context of osteogenesis [24][25][26]. It has been demonstrated that the incorporation of Ba 2+ into bioceramic compositions enhances the mineralization of their surfaces under in vitro conditions, as observed during immersion in simulated body fluid (SBF) [26][27][28][29][30]. One such oxide ceramic mineral phase, which includes silicon, calcium, and barium, is known as walstromite.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) printing is often used for industrial applications due to its flexibility and capability to provide ample mechanical strength and support after fabrication [ 1 ]. Furthermore, 3D printing is cost- and time-efficient and can provide design versatility [ 2 , 3 , 4 ]. It can fabricate scaffolds with lattice-like structures, providing weight reduction and ample mechanical strength and stiffness for numerous engineering applications such as automobile, aerospace, and biomedical engineering [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%